Surface driven nano-morphology of poly 3-hexylthiophene film, and their photophysical, spectral and electronic traits - Pandey, R.K.; Bisht, H.; Yadav, S.K.; Singh, A.K.; Prakash, R.; Mishra, H. (Elsevier Ltd, 2020)
The present paper compiles, the substrate driven nano-morphology of fluorescent semiconducting poly 3-hexylthiophene (P3HT) polymer films and their effects on photophysical, spectral, and electronic behaviour. Surface morphological study reveals regular long sized aggregation and large crystalline structure of polymer thin film in liquid surface grown (LSG) film as compared to hard surface grown (HSG) film. Experimentally observed and computationally simulated Raman spectra show that HJ coupling dominates in LSG film compared to HSG film. LSG film yields the structured electronic absorption and emission spectra with increased radiative decay time, in comparison to HSG film. These indicate a decrease of non-radiative transitions in LSG film and support more crystalline nature of the P3HT film as well as improve intrinsic mobility and device parameters in the sandwiched structure of Schottky diode configuration. The findings show that LSG based electronic/photonic devices have a high potential for enhanced performance at a little cost. © 2020
Keywords: P3HT fluorescent semiconducting polymer; Liquid substrate; Aggregation; Nano-morphology; Electronic structure; Charge transport